Community Service Empowerment of Agricultural Products - Widyasmoro Widyasmoro; Zuhud Rozaki (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Dusun Dlingseng is located in Banjaroyo Village, Kalibawang District, Kulon Progo Regency, which is the location of regular and international KKN in February and March 2019, where the majority of villagers rely on their main livelihood as farmers and ranchers. In addition to these two sources of livelihood, Dusun Dlingseng is also where the Banjaroyo Embung operates or often known as a mini reservoir. Where apart from being a place of recreation, this Embung and its surroundings are a place for the Dlingseng community to sell their garden produce. Agricultural products produced in Dlingseng Hamlet such as cassava, coffee, corn, cassava, coffee, rambutan, coconut, durian and others are grown on the farmers' respective lands. Usually they process cassava into "slondok" a typical Kulon Progo snack. They sell their products in the nearest market or at collectors who come at a low price. This community service is needed by the village with a program that supports the progress of the Dlingseng hamlet in processing existing natural resources and a program to train them to promote their production and sell them other than in the market in order to get more profit.